Respon Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays Saccharata) Aplikasi Pupuk NPK dan Limbah Cair Pabrik Kelapa Sawit - Muhammad Afrillah; Chairudin Chairudin; Monika Riski (Universitas Teuku Umar, 2023)
Sweet corn (Zea mays saccharata) is a staple food substitute for rice that is widely consumed by the people of Indonesia. To increase growth and production, fertilization needs to be done, one of which is the addition of palm oil liquid waste and also NPK fertilizer. This study aims to determine the dose of NPK and palm oil effluent for the growth and yield of maize. The research was carried out in the experimental garden of the Faculty of Agriculture, Teuku Umar University, West Aceh Regency. The study was conducted from December 2021 to February 2022. This study used a 2 x 4 factorial randomized block design (RAK) with 3 replications consisting of two factors. The factors studied include: NPK fertilizer (P) consists of 2 levels, namely: P1 (1.8 g), P2 (3.6 g). Dosage of Palm Oil Mill Liquid Fertilizer (L) consists of 4 levels, namely: L0 (Control), L1 (300 ml), L2 (450 ml), L3 (600 ml). Parameters observed were plant height, stem diameter, number of leaves, length of cob, weight of corn cobs with cob per cob, weight of corn cobs with cob per plot, weight of corn cobs without husks per cob, and weight of corn cobs without husks per plot. The results of the F test analysis of variance showed that the application of NPK fertilizer had a significant effect on plant height parameters 35 and 49 DAP, stem diameter parameters 49 DAP, number of leaves 35 DAP, corn cob length, corn cob weight per plot, and corn cob weight without husks. per plot, but had no significant effect on the weight parameter of corn cobs with cob per cob, and weight on corn cobs without husks per cob. The results of the variance test showed that the administration of palm oil effluent at various doses had no significant effect on all the parameters tested. The interaction effect between NPK fertilizer and palm oil mill effluent did not give a real interaction.